KONFLIK SOSIAL TABU NIKAH PADA MASYARAKAT PERDESAAN DI PURBALINGGA DAN BANYUMAS - Sugeng Priyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
This study is aimed at discovering the social conflicts which the community experienced leading to the marriage taboo. The study employs the historical method combined with the folklore and philological method. The two later methods are applied to provide the historical sources contained in the texts and folklores. Then, the historical method is taken to produce a historiography work, i.e. the cultural history or the intellectual history in the local range of Purbalingga and Banyumas. The results of study show that the marriage taboo in the rural community of Purbalingga and Banyumas indicates the phenomenon of plural socio-culture laid on socio-political legitimate. The marriage taboos are inflicted by social conflict as the manifestation of incest marriage, social rivalry, and legitimate battle. In those conflicts, the communities of Onje, of Banjaranyar, and of Raden Kaligenteng are the troublemakers. In addition, the communities of Sambeng Kulon, of Sambeng Wetan, of Jompo Kulon, and of Jompo Wetan can also be categorized into the troublemaker, since they are involved in the internal conflict, leaving them broken into parts. The marriage taboos indicate something that can be understood as the shift of cosmos into chaos. The chaotic situation is dominant, for the shift has not resulted in a new cosmos, i.e. it is always in the liminal or threshold position.